Peningkatan Strategi Pemasaran UMKM Jajanan Chikats Menggunakanakan E-Commerce : Studi Kasus UMKM Di Condong Catur, Yogyakarta - Febi Tornado; Yudas Tadius AC (Jurnal Pelayanan Hubungan Masyarakat, 2023)
This study aims to identify the extent of the role of e-commerce as a means to increase sales and marketing of MSMEs products, especially for home-based businesses, in Condong chess, Yogyakarta. This research uses a descriptive qualitative research type. The data sources used in this study are primary data sources and secondary data. The procedure for collecting data is by observation, interviews, and documentation. Data analysis in this study is data reduction, data presentation, withdrawal and conclusions. The results of the study show that the use of e-commerce as a promotion and sales channel is very important to increase sales and marketing of MSMEs products, one of which is a culinary business which is still relatively small. From the conclusions obtained, MSMEs Jajanan Chikats has practiced a marketing strategy by taking advantage of technological advances, namely by using e-commerce in the form of marketing media through Instagram and Shopee. This strategy has in fact penetrated the sales progress of MSMEs of Chikats snacks and expanded sales relations.